Risks and benefits of youth sport specialization: Perspectives and recommendations - Wiersma, L. D. (Pediatric Exercise Science, 2000)
Of growing concern to sport researchers is the practice of youth sport athletes specializing in sport at a young age. Sport specialization is characterized by year-round training in a single sport at the exclusion of other sport or nonsport activities. The purpose of this paper is to discuss the potential benefits of specialized sport at an early age in light of the potential risks associated with specialized participation. Three areas of consideration are discussed, including motor skill acquisition and performance, potential sociological consequences, and psychological concerns related to high-intensity training of young athletes. Finally, recommendations for further research and practical considerations are suggested for deciding the appropriateness of specialized sport in the training and development of youth sport athletes.